Granulocyte-macrophage colony-stimulating factor reduces lung bacterial load following traumatic brain injury and hemorrhage polytrauma in a juvenile rat model - Ghaith A. Bahader; Timothy Warner; Mark W. Hall; Eric A. Sribnick (PLoS ONE, 2025)
Traumatic brain injury (TBI) in children is associated with high rates of morbidity and mortality. Nosocomial respiratory infections are common following severe TBI, especially with polytraumatic TBI. Although post-injury immunosuppression has been identified as a potential contributor to nosocomial infection, the underlying mechanism and optimal therapy are poorly understood. In this study, we used a combined model of TBI plus extra-cranial hemorrhage followed by intranasal inoculation with Streptococcus pneumoniae to model the clinical scenario of polytrauma TBI and post-injury infection. Briefly, 28-day (prepubescent) rats received either sham injury or prefrontal controlled cortical impact injury plus removal of 25% of blood volume through femoral cannulation. Saline or 50µg/kg granulocyte-macrophage colony-stimulating factor (GM-CSF) was administered intraperitoneally daily for 2 days. Post-injury immune response was assessed in the blood, spleen, and brain using different immunologic techniques, while bacterial clearance was examined by plating lung tissue. Our results show that GM-CSF enhanced innate immune function by increasing the percentage of blood monocytes expressing elevated levels of MHC II molecules. GM-CSF also significantly increased splenic CD3 + T-cells, compared to the saline-treated injury group. Moreover, increased lung bacterial load (colony-forming units) was significantly reduced with GM-CSF treatment. Treatment with GM-CSF was not associated with an increase in brain glial activation, neuronal loss, or memory dysfunction. This study highlights the potential role of GM-CSF as a therapy to address the increased risk of nosocomial infections following polytraumatic TBI.